The Relationships among Self-esteem, Social Support, Severity of Skin Complication, Urinary Diversion Type and Quality of Life in Long term Urinary Diversion Patients - Ittipongwat, Thikumporn; Danaidutsadeekul, Suporn; Thosing, Orapan; Amornvesukit, Teerapon (Nursing Science Journal of Thailand, 2013)
Purpose: To explore the relationships among self-esteem, social support, severity of skin complication, urinary diversion type and quality of life in patients with long term urinary diversion. Design: Descriptive correlational research. Methods: The sample comprised 85 patients who underwent long term urinary diversion and came for their first or second follow-up care visit at the out-patient urological clinics residing in three tertiary care hospitals in Bangkok, Thailand. The data collection instruments comprised demographic data form, a self-esteem questionnaire, a social support questionnaire, a severity of skin complication observation form, and a quality of life questionnaire. Descriptive statistics, Pearson product moment, spearman rank orders and point biserial correlations were employed for statistical analysis. Main findings: The sample had ileal conduit type 54.1%, followed by 32.9% of percutaneous nephrostomy. The results revealed that their self-esteem and social support were at a moderate level. In regard to type of urinary diversion, 60% had urinary diversion without catheter while 40% with catheter. The majority of them (52.9%) did not have periostomy skin complication (level 0) while the remainders had level 1 and 2 of the severity. The quality of life was reported to be at a moderate level. Self-esteem had a positively moderate correlation with quality of life (r = .34, p < .01). Social support had a positively low level correlation with quality of life (r = .2, p < .05). Neither the type of urinary diversion nor the severity of skin complication was correlated with quality of life. Conclusion and recommendations: In order to facilitate smooth transition among patients with long term urinary diversion to better quality of life, nursing intervention to enhance the patients’ selfesteem and social support should be developed. Keywords: quality of life, self-esteem, skin complication, social support, urinary diversion บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาความสัมพันธ์ระหว่างความรู้สึกมีคุณค่าในตนเอง แรงสนับสนุนทางสังคม ความรุนแรงของภาวะแทรกซ้อนผิวหนัง ชนิดทางเดินปัสสาวะ และคุณภาพชีวิตของผู้ป่วยทำทางเดินปัสสาวะใหม่ระยะยาว รูปแบบการวิจัย: การวิจัยครั้งนี้เป็นการวิจัยเชิงบรรยายความสัมพันธ์ วิธีการดำเนินการวิจัย: คัดเลือกกลุ่มตัวอย่างแบบสะดวก มีอายุตั้งแต่ 15 ปีขึ้นไป มาตรวจตามนัดภายหลังผ่าตัดครั้งที่ 1 หรือครั้งที่ 2 ตั้งแต่เดือนสิงหาคม พ.ศ. 2554 ถึงเดือนมีนาคม พ.ศ. 2555 ได้กลุ่มตัวอย่างทั้งหมด 85 ราย จากโรงพยาบาลตติยภูมิ 3 แห่ง เครื่องมือรวบรวมข้อมูลประกอบด้วย 1) แบบสอบถามข้อมูลส่วนบุคคล 2) คุณภาพชีวิตผู้ป่วยทำทางเดินปัสสาวะใหม่ระยะยาว 3) ความรู้สึกมีคุณค่าในตนเอง 4) แบบสัมภาษณ์แรงสนับสนุนทางสังคม 5) แบบสังเกตความรุนแรงของภาวะแทรกซ้อนผิวหนัง วิเคราะห์ข้อมูลโดยการใช้ค่าสัมประสิทธิ์สหสัมพันธ์เพียร์สัน ค่าสัมประสิทธิ์สหสัมพันธ์สเปียร์แมน และค่าสหสัมพันธ์พอยท์ไบซีเรียล ผลการวิจัย: พบกลุ่มตัวอย่างที่ทำทางเดินปัสสาวะใหม่ระยะยาวชนิด ileal conduit ร้อยละ 54.1 รองลงมาเป็นชนิดpercutaneous nephrostomy ร้อยละ 32.9 มีความรู้สึกมีคุณค่าในตนเอง และแรงสนับสนุนทางสังคมระดับปานกลาง ทางเดินปัสสาวะใหม่เป็นชนิดไม่มีสายร้อยละ 60 และมีสายร้อยละ 40 ความรุนแรงของภาวะแทรกซ้อนผิวหนัง พบผิวหนังที่ไม่มีการเปลี่ยนแปลง (ระดับ 0) มากที่สุดร้อยละ 52.9 รองลงมาเป็นความรุนแรงระดับ 1 และ 2 ตามลำดับ และคุณภาพชีวิตผู้ป่วยทางเดินปัสสาวะใหม่ระยะยาวอยู่ในระดับปานกลาง ความรู้สึกมีคุณค่าในตนเองกับคุณภาพชีวิตมีความสัมพันธ์ทางบวกในระดับปานกลาง (r = .34, p < .01) แรงสนับสนุนทางสังคมมีความสัมพันธ์ทางบวกกับคุณภาพชีวิตระดับต่ำ (r = .2, p < .05) ส่วนความรุนแรงของภาวะแทรกซ้อนผิวหนังและชนิดทางเดินปัสสาวะไม่มีความสัมพันธ์กับคุณภาพชีวิต สรุปและข้อเสนอแนะ: พยาบาลควรพัฒนาโปรแกรมส่งเสริมความรู้สึกมีคุณค่าในตนเองและแรงสนับสนุนทางสังคมเพื่อการเปลี่ยนผ่านไปสู่คุณภาพชีวิตที่ดีของผู้ป่วยทำทางเดินปัสสาวะใหม่ระยะยาว คำสำคัญ: คุณภาพชีวิต ความรู้สึกมีคุณค่าในตนเอง แรงสนับสนุนทางสังคม ภาวะแทรกซ้อนผิวหนัง ผู้ป่วยทำทางเดิน ปัสสาวะใหม่